LARVICIDAL POTENTIAL OF INDIGOFERA TINCTORIA (FABACEAE) ON DENGUE VECTOR (AEDES AEGYPTI) AND ITS ANTIMICROBIAL ACTIVITY AGAINST CLINICAL ISOLATES - Srinivasan, Sakthivel; Wankhar, Wankupar; Rathinasamy, Sheeladevi; Rajan, Ravindran (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â antimicrobial efficacy against clinical isolates. Methods: The extract was tested at various concentrations 64, 128, 256, and 512 mg/ml for antimicrobial activity and 0.1 and 5 mg/L were prepared for larvicidal activity. The numbers of dead larvae were counted after 24 hrs of exposure. Result: The lowest minimum inhibitory concentration (MIC) values of the extract were 128 mg/ml against Klebsiella spp. - 1 alone and rest of the clinical test pathogens execute MIC activity at 512 mg/ml. The extract also showed antifungal activity with MIC of 64 mg/ml against the Candida albicans. Larvicidal activity of I. tinctoria extract were tested against fourth instar larvae A. aegypti and larval mortality were found after 24 hrs with lethal concentration (LC50)=3.1870 and LC90=5.3991 were observed. Conclusions: These results indicated that the extract displayed larvicidal potential on A. aegypti and antimicrobial activity against clinical isolates. Keywords: Infectious disease, Indigofera tinctoria, Antimicrobial activity, Larvicidal activity.